The Last Mughal : The Fall of A Dynasty, Delhi, 1857 - Dalrymple, William (Gurgaon, India Penguin Books, 2007)
The Last Mughal highlights Dalrymple's longstanding fascination with the Indian city of Delhi. It presents the Delhi that formed the seat of the Mughal empire in India - a city as brilliant as the monarch who reigned over it. Indeed Bahadur Shah Zafar II embodied the very essence of Delhi city. He was a talented and versatile individual, well-versed in poetry, calligraphy, and mysticism. Despite being under the control of the East India Company to quite an extent, he nevertheless managed to form a dazzling court, setting the stage for one of India's most culturally rich phases.In 1857, the Sepoy Mutiny that shook the vast British empire had its roots in the small rebellion staged by Indian troops in the East India company - a rebellion that had Zafar's approval. The final uprising had far-reaching consequences for the Indians as well as the British. In the aftermath of the uprising, the Mughal empire lay in complete shambles amidst heartbreaking blood and gore. The peaceful, once powerful emperor could only watch in helplessness and grief as his beloved empire was irrevocably lost.Dalrymple has crafted the book with great care, by conducting in-depth research and paying attention to local sensibilities. He has even succeeded in capturing the prosperous, poetic vibe of the Mughal empire.
The Fall of A Dynasty, Delhi, 1857.
Keywords: India--Delhi -- Sepoy Rebellion (India :--1857-1858) -- Muhammad Bahadur Shah II, King of Delhi, 1775-1862 -- Siege of Delhi (India : 1857)